Sintomas auditivos e desordens temporomandibulares - Pita, Murillo Sucena; Ribeiro, Adriana Barbosa; Zuim, Paulo Renato Junqueira [UNESP]; Garcia, Alicio Rosalino [UNESP] (My University, 2010)
Introduction: A variety of hypotheses have been proposed to explain the association between temporomandibular disorders and hearing symptoms, including the many anatomical and/or neurological ways, as of a muscle or joint dysfunction, can cause such symptoms. Objective: The purpose of this study is to discuss, through a systematic review of literature, the interrelation between hearing symptoms and temporomandibular disorders. Material and Methods: We consulted the Medline/PubMed, ISI and Scielo in the period 1918 to 2008. The terms related to the research were: “temporomandibular disorders”, “signs and symptoms of temporomandibular disorders”, “otologic symptoms” and “aural symptoms”, where 19 papers were included using the pre-selected criteria for the manufacture of a meta-analysis. Results: According to the findings, the hearing symptoms most often associated with temporomandibular disorders were otalgia and tinnitus, followed by vertigo and hearing loss, respectively. Conclusions: It’s clear the correlation between hearing symptoms and temporomandibular disorders, however there is a need clinical and scientific research more complex to prove the specific cause-effect relationships between them.

Introdução: Uma variedade de hipóteses tem sido propostas para esclarecer a associação entre desordens temporomandibulares e sintomas auditivos, entre elas as múltiplas possibilidades anatômicas e/ou neurológicas que, a partir de uma disfunção muscular ou articular, podem acarretar tais sintomas. Objetivo: O propósito do presente estudo é discutir, através de uma revisão sistemática de literatura, a inter-relação entre os sintomas auditivos e as desordens temporomandibulares. Material e Método: Foram consultados os indexadores Medline/PubMed, ISI e Scielo, no período de 1918 a 2008. Os termos relacionados para a pesquisa foram: “temporomandibular disorders”, “signs and symptoms of temporomandibular disorders”, “otologic symptoms” e “aural symptoms”, onde 19 artigos foram incluídos através dos critérios pré-selecionados para a confecção de uma metaanálise. Resultados: Segundo os dados encontrados, os sintomas auditivos mais freqüentemente relacionados com desordens temporomandibulares foram otalgia e zumbido, seguido de vertigem e perda auditiva, respectivamente. Conclusões: Torna-se evidente a correlação entre os sintomas auditivos e as desordens temporomandibulares, entretanto há a necessidade de pesquisas clínico-científicas mais complexas para comprovarem as específicas relações causa-efeito entre ambos.
Hearing symptoms and temporomandibular disorders
Keywords: Temporomandibular joint disorders; Temporomandibular joint dysfunction syndrome; Hearing disorders; Transtornos da articulação temporomandibular; Síndrome da disfunção da articulação temporomandibular; Transtornos da audição